Poly(Anthraquinonyl Sulfide)/CNT Composites as High‐Rate‐Performance Cathodes for Nonaqueous Rechargeable Calcium‐Ion Batteries - Siqi Zhang (Advanced Science, 2022)
Abstract Calcium‐ion batteries (CIBs) are considered as promising alternatives in large‐scale energy storage due to their divalent electron redox properties, low cost, and high volumetric/gravimetric capacity. However, the high charge density of Ca2+ contributes to strong electrostatic interaction between divalent Ca2+ and hosting lattice, leading to sluggish kinetics and poor rate performance. Here, in situ formed poly(anthraquinonyl sulfide) (PAQS)@CNT composite is reported as nonaqueous calcium‐ion battery cathode. The enolization redox chemistry of organics has fast redox kinetics, and the introduction of carbon nanotube (CNT) accelerates electron transportation, which contributes to fast ionic diffusion. As the conductivity of the PAQS is enhanced by the increasing content of CNT, the voltage gap is significantly reduced. The PAQS@CNT electrode exhibits specific capacity (116 mAh g−1 at 0.05 A g−1), high rate capacity (60 mAh g−1 at 4 A g−1), and an initial capacity of 82 mAh g−1 at 1 A g−1 (83% capacity retention after 500 cycles). The electrochemical mechanism is proved to be that the PAQS undergoes reduction reaction of their carbonyl bond during discharge and becomes coordinated by Ca2+ and Ca(TFSI)+ species. Computational simulation also suggests that the construction of Ca2+ and Ca(TFSI)+ co‐intercalation in the PAQS is the most reasonable pathway.